2022
DOI: 10.2196/37302
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Engagement With a Cognitive Behavioral Therapy–Based Conversational Agent (Wysa for Chronic Pain) Among Adults With Chronic Pain: Survival Analysis

Abstract: Background Digital applications are commonly used to support mental health and well-being. However, successfully retaining and engaging users to complete digital interventions is challenging, and comorbidities such as chronic pain further reduce user engagement. Digital conversational agents (CAs) may improve user engagement by applying engagement principles that have been implemented within in-person care settings. Objective To evaluate user retention … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…These high rates of engagement and retention indicate that the participants found the app features helpful for their everyday challenges 38 . The app’s CA has also demonstrated the ability to create a therapeutic alliance, which has also been positively linked with user engagement 39 …”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…These high rates of engagement and retention indicate that the participants found the app features helpful for their everyday challenges 38 . The app’s CA has also demonstrated the ability to create a therapeutic alliance, which has also been positively linked with user engagement 39 …”
Section: Discussionmentioning
confidence: 91%
“… 38 The app’s CA has also demonstrated the ability to create a therapeutic alliance, which has also been positively linked with user engagement. 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study involving Wysa users reported a significantly higher average improvement in depressive symptoms among the high-engagement Wysa user group compared to that of the low-engagement Wysa user group [ 19 ]. Additionally, Wysa has been found to improve mental health outcomes in chronic conditions [ 20 , 21 ], with high engagement and adherence [ 22 ]. It was found that users were able to establish a strong therapeutic alliance with the AI-based conversational agent that was comparable to a human therapeutic bond [ 23 ], further confirming the positive feedback from users [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Closer to our proposal, some works allow free language input. Wysa chatbot [ 41 , 42 ] works with free natural language or just a multiple-choice input, depending on the dialogue state. As for the output, unrestricted responses in complex dialogues can be found in EVA, MIRA and AMANDA [ 43 , 44 , 45 ], which are virtual medical assistants developed within the RASA ( , accessed on 20 January 2023) framework.…”
Section: Related Workmentioning
confidence: 99%